2020
DOI: 10.3390/foods9040510
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Model System for Tasting Grain Varieties

Abstract: This study investigated suitable approaches and effective applications for the evaluation of grain flavor differences among cultivars. A model system that helps to facilitate the characterization of flavors in grain varieties was developed using sorghum grain as a tool. Five different applications were initially used, including cooked grain, porridge, cookies, muffins, and extruded puffed snacks. Six highly trained sensory panelists participated in the project. The effectiveness of each application was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Only two studies were found that used pressure cooking that also verified the sensory acceptance. Tran and Chambers [31] looked at five products made with commercially available sorghum using different processes (cooked grains, porridge, cookies, muffins and extruded puffed snacks) and, through the sensory analyses, verified that cooked sorghum grains and the cookies made with sorghum flour presented distinct flavor attributes, being recognized as the samples with the greatest flavor of the original grain. Hicks-Roof et al [32] tested cooked grains with college students and concluded from the comparative sensory analyses that the cooked sorghum was as well accepted as cooked refined rice, being a good option to replace the refined cereals and contribute to an increase in whole grain consumption.…”
Section: Wet Cooking: Common and Pressure Methodsmentioning
confidence: 99%
“…Only two studies were found that used pressure cooking that also verified the sensory acceptance. Tran and Chambers [31] looked at five products made with commercially available sorghum using different processes (cooked grains, porridge, cookies, muffins and extruded puffed snacks) and, through the sensory analyses, verified that cooked sorghum grains and the cookies made with sorghum flour presented distinct flavor attributes, being recognized as the samples with the greatest flavor of the original grain. Hicks-Roof et al [32] tested cooked grains with college students and concluded from the comparative sensory analyses that the cooked sorghum was as well accepted as cooked refined rice, being a good option to replace the refined cereals and contribute to an increase in whole grain consumption.…”
Section: Wet Cooking: Common and Pressure Methodsmentioning
confidence: 99%
“…The same consensus approach was used as during the orientation and lexicon development phase. Consensus evaluation during testing is an effective way to ensure that key attributes, such as storage attributes or ones that have not be apparent in samples during lexicon development, can easily be added and scored consistently by the panelists [46] and has been used effectively for various products in published studies for many years [48][49][50][51][52][53][54]. When the panelists reached consensus on the attributes and intensities noted in that sample, testing was completed for that sample.…”
Section: Sample Evaluationmentioning
confidence: 99%